2017
DOI: 10.1063/1.4984117
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier tuning via dopant segregation in NiGeSn-GeSn contacts

Abstract: We present a comprehensive study on the formation and tuning of the Schottky barrier of NiGeSn metallic alloys on Ge 1-x Sn x semiconductors. First, the Ni metallization of GeSn is investigated for a wide range of Sn contents (x ¼ 0-0.125). Structural analysis reveals the existence of different poly-crystalline NiGeSn and Ni 3 (GeSn) 5 phases depending on the Sn content. Electrical measurements confirm a low NiGeSn sheet resistance of 12 X/(almost independent of the Sn content. We extracted from Schottky barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Moreover, Pt–GeSn showed better behavior in terms of thermal stability compared to Ni–GeSn and Ti–GeSn. Because Sn loss occurs during B-doped GeSn CVD growth, it is still challenging to create low contact resistivity p-type GeSn contacts with high Sn contents, a challenge that is particularly critical for GeSn lasers and GeSn TFETs [ 207 , 208 ].…”
Section: Research Progress For Gesn Cvd Growth and Its Potential Applicationsmentioning
confidence: 99%
“…Moreover, Pt–GeSn showed better behavior in terms of thermal stability compared to Ni–GeSn and Ti–GeSn. Because Sn loss occurs during B-doped GeSn CVD growth, it is still challenging to create low contact resistivity p-type GeSn contacts with high Sn contents, a challenge that is particularly critical for GeSn lasers and GeSn TFETs [ 207 , 208 ].…”
Section: Research Progress For Gesn Cvd Growth and Its Potential Applicationsmentioning
confidence: 99%
“…The Sn fractions in the NiGeSn and GeSn layers are ∼10% (Figure d). The average composition of Ni is ∼50.2% in the NiGeSn layer, and it suggests that a Ni 1 (GeSn) 1 phase is formed. For NiGe alloys, the Ni 1 Ge 1 phase contributes a lower sheet resistance and SBH than other phases such as Ni 2 Ge 1 and Ni 5 Ge 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…For high-performance applications, low series resistances such as source/drain (S/D) and contact resistances are needed. While a low contact resistivity of <10 –9 Ω·cm 2 has been demonstrated in a metal/p-GeSn contact, for metal/n-Ge­(Sn) contacts, their high electron Schottky barrier height (SBH) due to Fermi-level pinning (FLP) leads to a large contact resistivity of 10 –6 –10 –7 Ω·cm 2 . , Because of a large number of surface states in Ge­(Sn), the Fermi level is pinned near the valence band edge, resulting in a high SBH for electrons. , Understanding the SBH properties of the metal/n-GeSn contacts is critical to reduce the contact resistivity, and only few studies were reported on the electron SBHs. In those studies, the electron SBHs were obtained from the metal/n-GeSn contacts with low Sn fractions (0–3.4%), or they were indirectly extracted from the hole SBHs. , Ideally, the electron SBH is equal to the energy difference between the band gap and the hole SBH. The band gap energy needs to be determined precisely to extract the electron SBH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Ge NW device, possible boron deactivation 26 in the top Ge for smaller NWs and less B segregation during NiGe formation 27 cause rapid contact resistance increase as the NW diameter decreases. For GeSn/Ge NW p-FETs, a higher density of boron segregated at the NiGeSn/GeSn interface 28 and the smaller SBH of NiGeSn/GeSn result in lower contact resistance increasing rate with decreasing NW diameter, compared to the Ge p-FET. Next, the influence of the NW diameter scaling on the electrical characteristics of GeSn/Ge and Ge pFETs is studied by analyzing the dependence of SS and drain-induced-barrier-lowering (DIBL) on the NW diameters.…”
Section: Electrical Characterizationmentioning
confidence: 99%